Agentes tróficos na dieta de leitões desmamados sobre a atividade das enzimas digestivas e o desempenho - Tucci, Fernanda Marcussi; Thomaz, Maria Cristina [UNESP]; Pizauro Júnior, João Martins [UNESP]; Hannas, Melissa Izabel; Scandolera, Antônio João; Budiño, Fábio Enrique Lemos (My University, 2011)
It was evaluated the effect of the addition of glutamine, polyunsaturated fatty acids or cellular wall of yeast to the diet of weaned pigs on the activity of the pancreatic enzymes (lipase, amylase and trypsin) and the intestinal mucous membrane (dipeptidase, sucrase and maltase) and on the performance. Forty-five weaned pigs were used and distributed in a randomized block design, in factorial outline, with four diets (T1 - basal diet (BD); T2 - BR + 1% glutamine; T3 - BD + 0,2% cellular wall of yeast; T4 - BD + 5% fish oil) and two slaughter ages (seven and 14 days post weaning). The performance was measured in the first two weeks post-weaning. The addition of 1% glutamine in the diet of pigs increased the specific and total activity of the amylase, and total activity of the trypsin in the second week post weaning. The others supplements not change the activity of the digestive enzymes in the pigs. Also an increase was observed in the total activity of the lipase, and specific activity of the trypsin and maltase in function of the age post-weaning. In general, the activities of the digestive enzymes were correlated positively, except for the dipeptidase that was not correlated with any other enzyme. Positive correlation was observed between weight gain and activity of the lipase and of the amylase. The supplements included in the diet not influence the performance of weaned pigs.
Trofic agents in the diet of weaned pigs on the activity of the digestive enzymes and the performance
Keywords: Glutamine; Mucous membrane enzymes; Pancreatic enzymes; Polyunsaturated fatty acids; Prebiotic; Suidae